Health and health care concerns among women and racial and ethnic minorities - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald Publishing Limited, 2017)
This volume covers macro-level system issues and micro-level issues involving health and health care concerns for women, and racial and ethnic minorities. Topics covered include examination of health and health care issues of patients or of providers of care especially those related to concerns for women and for racial and ethnic minorities in different countries. This volume is divided into four sections. The first section introduces the volume. The second section covers women and reproductive related health and health care concerns, using data sources from the United States and the UK. The third section examines health care practitioners, health and health care, relating to issues of women or racial and ethnic minorities, using data sources from the US and Canada. The last section relates specifically to racial and ethnic minorities and health and health care. Chapters focus on Black men, on Asian Americans, on Mexican Americans, and across racial and/or ethnic differences.
Prelims -- Introduction to volume -- Women and reproductive related health and health care concerns -- Health care practitioners and health and health care -- Racial and ethnic minorities and health and health care -- About the editor -- Index.
Includes index.
Includes bibliographical references.
Keywords: Minority women -- Health and hygiene -- United States; Minorities -- Health and hygiene -- United States; Minority women -- Health and hygiene -- Canada; Minorities -- Health and hygiene -- Canada; Social Science -- Disease & Health Issues; Medical sociology